Objeto de aprendizagem e o estudo de gramática: uma perspectiva de aprendizagem significativa - Barbosa, Rita Cristiana (2008)
ABSTRACT The following work presents a reflection on the subjects of educational computing, the theory of meaningful learning and the study of grammar. Its research and analysis material comes from a digital object specially designed to detect meaningful learning through educational computing. The institutional material was elaborated following the teaching methodology based on David Ausubel's theory and the conceptual maps of Joseph Novak and Bob Gowin. The conceptual maps' strategy seeks to enrich the student's cognitive structures by inserting them in an active learning process. Ausubel affirms that the acquiring and retaining of knowledge are the product of an active process which integrates instruction materials with the student's own cognitive structure's relevant ideas. Following that ideal, this work describes the theoretical principles that serve as basis for the creational process of educational games as learning objects. We also consider Ausubel's meaningful learning theory and educational computing in the process of using the games to teach Portuguese language. The experimental research process had as its objective to measure, in a systematic way, the efficiency of an instrument designed to teach grammar concepts to students of 7th grade. The research subjects were divided in two groups (experimental and control), based on a pretest about morph syntactic analysis. Following the pretest, we worked with the experimental group during a period of fifteen (15) days. During this period we had sessions of pedagogical intervention using the digital instrument that contained grammar concepts in the format of an educational game. We also used hierarchical organization of learning concepts and conceptual maps with the experimental group, while the other group watched classes about the same subject given with standard methodology. When this period was over, it was applied a test to both groups. In the final evaluation, it was verified that the experimental group had markedly better results than the control group. Once considering that the control group hadn't experienced the digital instrument and the experimental group had, we believe that the results point to the efficiency of the instrument as a learning tool.